Flora exótica de Galicia (noroeste ibérico) - Romero Buján, María Inmaculada (Botanica Complutensis, 2007)
The introduction of species beyond their natural range is resulting from globalisation success and invasive alien species are considered the second cause of global biodiversity loss. In this sense, a check-list of 328 of introduced vascular plants in the Northwest of Iberian Peninsula is provided and specific information was analysed. The results indicate that 20 species are new for the Spanish Alien Flora and 80 species were identified as invasive species, 50% are American origin.
Keywords: Species invasions; Check-list alien plants; Floristic records; Spain